Moderation effect of social support and personal resources between emotional work and employee wellbeing. Issue 2 (4th March 2021) - Mehta, Poonam; Sharma, Jyoti
Abstract : Purpose: There is dearth of studies in the literature which have discussed the relevance of personal and social resources of employees to protect them from adverse impacts of emotional job demands. However, interaction effect of these two resources on wellbeing of the employees in context to emotional work is inadequate. The present study is aimed to address the existing gap and investigate the relevance of personal and social resources as moderators in the presence of each other between emotional work and employee wellbeing. Design/methodology/approach: The research work has focused on employees working on frontline profiles of civil aviation industry of north India. The responses of 720 frontline employees have been collected through pretested questionnaire. To understand the moderation effect of two variables, model number 3 developed by Hayes (2012) has been applied. Findings: The findings have revealed that moderator role of social support between emotional work and employee wellbeing. However, research has pointed out that at high level of social support personal resources of employees' start to decline which subsequently reduces the wellbeing of employees. Research limitations/implications: The present research work has analysed the moderated moderation effect of personal and social resources between emotional work and employee wellbeing. Besides, the relative significance of personal resources vis-a vis social resources empirically in context of employee wellbeing in case of emotional work has also been highlighted in the work. Practical implications: The results of the study have suggested the employees to receive less social support from friends, family and other significant relationships to protect their personal resources in emotional work settings. Moreover, research work has implicated for employers to draw out the various interventions through which personal resources of employees can be enhanced in emotional work settings. Also, the research has assisted in designing the key competencies for different job domains of emotional work setups. Social implications: The present study is very substantial in offering various parameters over which wellbeing policies for individuals can be framed. Also, the study has outlined the consequences of receiving different levels of social support which is applicable for that set of population who wants to enhance their personal resources for attaining high wellbeing. Originality/value: The study has empirically investigated interaction effect of social and personal resources of employees between emotional work and employee wellbeing which is scarce in the literature. Besides, a dark side of social support in emotional work context has also been highlighted which was scarcely discussed in emotional work settings previously.